The rural environmental registry in the Caraíva-Trancoso Environmental Protection Area and its importance for environmental conservation - Lopes, Elfany Reis do Nascimento; Pedra, Luysa Souza Oliveira (Technical and Scientific Journal Green Cities, 2025)
The research aimed to evaluate the adequacy of the Rural Environmental Registry (CAR) within the Caraíva-Trancoso Environmental Protection Area (APA), identifying its limitations and compliance with Law No. 12,651/2012. The spatial files of rural properties within the APA were acquired from the SICAR database for the year 2024, while state and municipal base files were obtained from IBGE (2021), and protected area files were collected from the MMA (2023). QGIS 3.28.6 software was used to conduct technical and comparative analyses of the APA. A total of 291 registered properties were identified within the Caraíva-Trancoso APA, covering an area of 12,850.60 ha, of which 289 properties were classified as “awaiting analysis” and 2 as “cancelled by administrative decision.” Properties smaller than 1 fiscal module account for approximately 3.81% of the total area of the APA, properties ranging from 1 to 4 fiscal modules make up 10.82%, and properties larger than 4 fiscal modules represent 25.65% of the total area of the Caraíva-Trancoso APA. The area with the largest number of declared rural properties is the Strict Protection Zone, followed by the Agricultural Zone. Regular RLs account for 2,464.15 ha, while irregular RLs account for 280.146 ha. APPs total 960.884 ha of regular areas and 93.93 ha of irregular areas. Overlaps of legal reserves were identified within the APPs, totaling 298.12 ha. This study enabled the assessment of the information provided in the national system, which will serve as a basis for monitoring the protected area by its management.
Keywords: Legal Reserve; Permanent Preservation Area; Protected Area